ChemInform Abstract: Microwave‐Assisted Palladium Mediated Efficient Synthesis of Pyrazolo[3, 4‐b]pyridines, Pyrazolo[3, 4‐b]quinolines, Pyrazolo[1, 5‐a]pyrimidines and Pyrazolo[1, 5‐a]quinazolines. Issue 4 (January 2015) - Shekarrao, Kommuri; Kaishap, Partha Pratim; Saddanapu, Venkateshwarlu; Addlagatta, Anthony; Gogoi, Sanjib; Boruah, Romesh C.
Abstract The reaction is conducted under environmentally benign conditions.